Effects of peripheral nerve stimulation on paralysed upper limb functional recovery in chronic stroke patients undergoing low-frequency repetitive transcranial magnetic stimulation and occupational therapy: A pilot study - Masanori Maeda; Hitoshi Mutai; Yumi Toya; Yusuke Maekawa; Takatoshi Hitai; Satoshi Katai (SAGE Publishing, 2020)
Objective Upper limb paralysis, which is a sequela of stroke, limits patients' activities of daily living and lowers quality of life. The objective of this study was to examine the effects of peripheral nerve stimulation on hemiparetic upper limb functional recovery in chronic stroke patients undergoing low-frequency repetitive transcranial magnetic stimulation and occupational therapy. Methods The subjects were chronic stroke patients who participated in a two-week inpatient programme including repetitive transcranial magnetic stimulation and occupational therapy. There were two groups of patients: the peripheral nerve stimulation group (11 patients who underwent peripheral nerve stimulation) and the control group (11 patients who previously participated in the same inpatient programme but without peripheral nerve stimulation, selected via propensity score matching). The peripheral nerve stimulation group had 1 h of peripheral nerve stimulation on the median and ulnar nerves during occupational therapy. The outcome measures were the Wolf Motor Function Test, Fugl-Meyer Assessment, and Motor Activity Log. Results Wolf Motor Function Test, Fugl-Meyer Assessment, and Motor Activity Log showed significant improvement after the intervention in the peripheral nerve stimulation group. Particularly, the Fugl-Meyer Assessment hand score significantly improved in the peripheral nerve stimulation group compared to that in the control group (median change: 2 versus 0; p = 0.021, r = 0.49). Conclusion The combined use of peripheral nerve stimulation with occupational therapy after repetitive transcranial magnetic stimulation may result in a better functional recovery of in hemiparetic upper limb. Peripheral nerve stimulation with stimulation above the sensory threshold and below the motor threshold is easy to combine with occupational therapy upper limb function training and is therefore clinically useful.